2021
DOI: 10.1111/1462-2920.15341
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bacterial communities in a municipal duck pond during a phytoplankton bloom and isolation of Anatilimnocola aggregata gen. nov., sp. nov., Lacipirellula limnantheis sp. nov. and Urbifossiella limnaea gen. nov., sp. nov. belonging to the phylum Planctomycetes

Abstract: Waterbodies such as lakes and ponds are fragile environments affected by human influences. Suitable conditions can result in massive growth of phototrophs, commonly referred to as phytoplankton blooms. Such events benefit heterotrophic bacteria able to use compounds secreted by phototrophs or their biomass as major nutrient source. One example of such bacteria are Planctomycetes, which are abundant on the surfaces of marine macroscopic phototrophs; however, less data are available on their ecological roles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Both, MLSA- as well as 16S rRNA sequence-based phylogeny ( Figure 8 and Supplementary S1 ) suggested that strain HG15A2 T is a member of the only recently proposed and then expanded planctomycetal family Lacipirellulaceae [ 42 , 63 , 114 ]. The placement as a new genus is supported by AAI and POCP values found to fall below (in a single case slightly above) the genus thresholds of 60–80% and 50%, respectively [ 84 , 110 ] ( Supplementary Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both, MLSA- as well as 16S rRNA sequence-based phylogeny ( Figure 8 and Supplementary S1 ) suggested that strain HG15A2 T is a member of the only recently proposed and then expanded planctomycetal family Lacipirellulaceae [ 42 , 63 , 114 ]. The placement as a new genus is supported by AAI and POCP values found to fall below (in a single case slightly above) the genus thresholds of 60–80% and 50%, respectively [ 84 , 110 ] ( Supplementary Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…All samples were transferred to the DSMZ, Braunschweig, Germany within 24 h and processed within 4 h after arrival. In the laboratory, 300 mL of the water samples were homogenized by gentle stirring and subjected to a two-step filtration process to separate aggregated/particle-attached and planktonic bacterial cells [ 42 ]. In the first step, the water was filtered through a borosilicate glass microfiber filter (Whatman GF/D, GE Healthcare, Dassel, Germany) with a pore size of 2.7 µm to retain aggregated cells and marine particles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we found that specific halogenase genes only presented in a particular collection of G. heterophylla roots. For example, cluster 2 ( Urbifossiella limnaea strain ETA A1) [ 25 ] occurred explicitly in the 2018 collection, whereas cluster 4 ( Streptomyces chartreusis strain ATCC 14922) [ 26 ] only appeared in the 2017 collection. On the contrary, we noticed that some halogenase genes presented in both groups, such as cluster 1 ( Catenulispora acidiphila strain DSM 44928), cluster 3 ( Variovorax sp.…”
Section: Resultsmentioning
confidence: 99%
“…They have been found previously abundant during intensive blooms 48 , 49 , with a preference to remain attached than free-living 50 . Furthermore, they are known to degrade complex polysaccharides, and therefore, it has been proposed that they feed on cyanobacterial exudates and decaying material 35 , 51 .…”
Section: Discussionmentioning
confidence: 99%